Work-Integrated Reflective Learning and Business Outcomes Among College Graduates - Roze, Jana; Vaičulena, Signe; Supe, Jānis; Šmite, Diāna; Rubene, Ilze; Roķe-Reimate, Līga (Proceedings for the European Conference on Reflective Practice-based Learning 2025, 2025)
Entrepreneurship is a key driver of economic development, and higher education plays a pivotal role in nurturing entrepreneurial potential. Multiple studies have examined the relationship between students’ entrepreneurial intentions and various individual and entrepreneurship support factors. However, relatively little attention has been paid to the role of work-integrated reflective learning in entrepreneurship and its relationship with other support factors, particularly in relation to the longevity of the entrepreneurial activities of the business programme’s graduates. The aim of this research is to investigate which educational factors related to work-integrated reflective learning along with individual factors of students predict the sustainability of entrepreneurship one year after graduation among alumni of the short-cycle professional higher education program in Micro, Small, and Medium Enterprise Management at the College of Business Administration (CBA) in Latvia. Survey data were collected from 67 graduates who completed the programme between 2019 and 2023. The data were analyzed using logistic regression analysis. The results show that two factors - entrepreneurial experience prior to studies and the perceived usefulness of business development skills acquired through work-integrated learning - significantly increased the likelihood of graduates maintaining an active business one year after graduation. Among the two, previous entrepreneurial experience emerged as the strongest predictor. The results provide important insight into how to support new entrepreneurs effectively during the initial years of their ventures. The findings may be useful for educational institutions in improving professional higher education programmes in entrepreneurship, especially in the design of internship programmes.